Adjunctive Hyperbaric Oxygen Therapy promotes successful healing in patients with refractory Crohn's disease - Feitosa,Marley Ribeiro (2016)
PURPOSE: To investigate de adjunctive effect of Hyperbaric Oxygen Therapy in a group of patients with refractory Crohn's disease. METHODS: A total of 29 subjects with refractory Crohn's disease were submitted to daily sessions of Hyperbaric Oxygen Therapy, in a 2800 Sechrist Monoplace Hyperbaric Chamber (Sechrist, USA) pressurized to 2.4 ATA. Each session lasted 2 hours. The endpoint was closure of enterocutaneous fistulas and complete healing of Pyoderma Gangrenosum and perineal Crohn's disease. RESULTS: A total of 829 HBOT sessions were performed and no complications were noted. Overall success rate was 76% (22 cases). Pyoderma Gangrenosum and enterocutaneous fistulas had the highest successful healing rates (100% and 91%, respectively). Perineal Crohn's disease healing rate was 65%. CONCLUSION: Adjunctive Hyperbaric Oxygen Therapy promoted satisfactory healing in a group of patients with refractory Crohn's disease.